2022
DOI: 10.1155/2022/7768963
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA ZFAS1 Protects HK-2 Cells against Sepsis‐Induced Injury through Targeting the miR3723p/PPARα Axis

Abstract: In septic acute kidney injury, one of the main purposes of long noncoding RNA (lncRNA) ZFAS1 is still unclear. This study is intended to analyze the effects of lncRNA ZFAS1 on the septic AKI in the HK-2 cell line. Materials and Methods. In order to construct an in vitro model of septic AKI, HK-2 cells have been treated with lipopolysaccharides. CCK-8 assay has been utilized to check the viability of HK-2 cells. The contents of inflammatory cytokines (that includes IL-1β, TNF-α, and IL-6) have been marked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Cells were seeded onto 96-well plated supplied with a completed culture medium incubating at 7°C with the same gas atmosphere as cell culture. After 24, 48, and 72 h of incubation, cell counting kit-8 reagent (CCK8, Dojindo, Japan) was added to each well and incubated for another 2 h. The absorbance of each well at 450 nm was measured plotting the OD 450 -time curve to assess cell growth [26].…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Cells were seeded onto 96-well plated supplied with a completed culture medium incubating at 7°C with the same gas atmosphere as cell culture. After 24, 48, and 72 h of incubation, cell counting kit-8 reagent (CCK8, Dojindo, Japan) was added to each well and incubated for another 2 h. The absorbance of each well at 450 nm was measured plotting the OD 450 -time curve to assess cell growth [26].…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%